IMPLIKATUR PERCAKAPAN YANG DITEMUKAN DALAM DIALOG FILM THE SIXTH SENSE OLEH M. NIGHT SHYAMALAN - Pratama, Yudi Apriandi; Anayati, Wan (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2022)
This research is aimed to analyze the conversational implicatures and the application of cooperative principle found in the dialogues of The Sixth Sense movie. The analysis based on qualitative methodology which focused on four kinds of maxims (P. Grice, 1975). The next section is the analysis of the dialogues which contained cooperative principle. The result of this research shows seventeen maxim violations included eight of data violating a maxim of quality, three data violating maxim of quantity, three data violating maxim of manner, and three data violating maxim of relevance. The researcher also found six data of cooperative principle in the object of the research. The theory successfully applied towards the data of maxim violations and cooperative principle in The Sixth Sense movie.